Clinical Profile and Treatment Outcome of H-mono/Polydrug-resistant Tuberculosis: A Single-center Retrospective Study - Shital Kabra; Snehal Jadhav (Journal of Advanced Lung Health)
Background: Isoniazid-monoresistant tuberculosis (Hr-TB) is the most prevalent drug-resistant TB. It often precedes multidrug-resistant TB (MDR-TB) and poses a major threat in the fight against TB control. The treatment outcome in Hr-TB and polydrug-resistant TB (PDR-TB) other than MDR still remains unclear. Aim: The aim of the study is to determine the clinical characteristics and treatment outcome in H-mono/PDR-TB under programmatic conditions. Materials and Methods: The study design was retrospective observational. It was conducted at the respiratory medicine department of a tertiary care institute in Mumbai. The medical records for bacteriologically confirmed TB patients diagnosed between July 2021 and December 2022 were reviewed. A total of 827 patients were enrolled and among them 46 patients with H-mono/PDR-TB were analyzed. The demographic data, clinical characteristics, and treatment outcomes were recorded. Results: Among 46 patients of isoniazid mono-resistant/PDR-TB analyzed from 827 bacteriologically confirmed TB, 24 were women with a mean age of 30.5 years. Twenty-five (54.34%) were resistant to isoniazid and the remaining 21 (45.66%) were PDR-TB. Primary Hr-TB was detected in 43 (93%) patients. The KatG mutation in 30 (65.2%) patients was the most common form of isoniazid (INH) mono resistance followed by inhA mutation 16 (34.8%). The fluoroquinolone (FQ)-based treatment regime as per national program guidelines had favorable outcomes in 42 (91.3%). However, unfavorable outcome with progression to MDR was observed in 3 (6.52%) and death in 1 (2.18%) patients. Conclusion: H-mono/PDR-TB is the most prevalent DRTB and most of them have primary resistance to isoniazid. Availability of first and SL LPA and limited DST with FQ-based regime under the national program has improved treatment outcomes in Hr-TB/PDR-TB.